Designing an Empowerment Model for Iranian Health Centre Managers: A comprehensive study - Fatemeh Yousef Yaghoobi; Leila Riahi; Seyed Jamaleddin Tabibi; Mahmood Mahmoodi Majdabadi Farahani (ACHSM, 2020)
OBJECTIVES: Empowering managers plays a crucial role in developing the capabilities and competencies of individuals to improve the continuous performance of health center organizations. The purpose of this study is to design a model of empowerment of health center managers in Iran during 2018-2019. DESIGN: In this applied, exploratory and cross-sectional study, human resource empowerment components were extracted by reviewing the literature and interviewing subject specialists. Then, the conceptual model of the research was designed and the questionnaire was formulated and validated. Data were collected by filling out a questionnaire from a total of 416 managers of health centers selected by stratified random sampling. The collected data were analyzed using descriptive statistics and confirmatory and exploratory factor analysis. RESULTS: In the final model of empowerment of health center managers, five factors were identified as effective factors. The standardized regression coefficients among the contextual, self-efficacy, managerial, organizational-value, and psychological factors with empowerment were 0.98, 0.95, 0.92, 0.90, and 0.76, respectively. The results of confirmatory factor analysis indicate the suitability of the final model of health center managers' empowerment. CONCLUSIONS: Due to the influence of contextual, self-efficacy, managerial, organizational-value, and psychological factors in the model approved in this study, the health system senior managers can have a systemic approach to issues. In addition, they can improve managers' abilities by employing a continuous self-assessment system in health centers, applying the proposed model, improving administrative infrastructure and working environment, paying attention to organizational culture, reward system, participatory management, information sharing, continuous training, and modeling.